Modeling the Hydrolysis of Soybean Flour Proteins Digested with Gastric Proteases of the Marine Fish Sparus aurata and Commercial Non-Starch Polysaccharidases - Óscar Martínez; Lorenzo Márquez; Francisco J. Moyano; Manuel Díaz (Fishes, 2025)
Soybean flours are widely used as a protein-rich ingredient in fish aquafeeds, and to obtain value-added compounds after a previous treatment with proteases. Additionally, non-starch polysaccharidases (NSPases) enhance dietary protein bioaccessibility and have been used as feed additives. In this study, defatted soybean flour was hydrolyzed using Sparus aurata gastric proteases and varying doses of a commercial blend of acidic NSPases. Reactions occurred at 25 °C for 3 h under typical fish stomach pH conditions (3.5–5.6). We modeled the hydrolytic process using response surface methodology, focusing on the released peptides and carbohydrates. The main finding was the efficient control of the degree of protein hydrolysis. We achieved 6–25% hydrolysis for peptides below 10 kDa by adjusting the carbohydrase dose and reaction pH. This work confirms that acidic commercial NSPases improve soybean flour protein hydrolysis when combined with S. aurata gastric proteases.